2014
DOI: 10.1007/s00270-014-0975-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Peripherally Implanted Venous Access Ports in the Forearm in Female Cancer Patients

Abstract: Peripherally implanted venous access ports in the forearm are a safe alternative to chest or upper-arm ports in female oncology patients. Special attention should be paid to signs of skin dehiscence and nonthrombotic dysfunction, especially when used for long-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Twenty-one 7,8,20,22,25,36,39,41,42,48,55,61,64,68,69,71,75,76,92,94,95 of the 69 noncomparison studies (23 cohorts, n = 12 265) reported VTE by number of thrombosis per 1000 catheter-days. Within these studies, the pooled rate of VTE was 0.08 (95% CI: 0.06-0.10) per 1000 catheter-days ( Figure S2).…”
Section: The Incidence Of Tivap-related Vtementioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-one 7,8,20,22,25,36,39,41,42,48,55,61,64,68,69,71,75,76,92,94,95 of the 69 noncomparison studies (23 cohorts, n = 12 265) reported VTE by number of thrombosis per 1000 catheter-days. Within these studies, the pooled rate of VTE was 0.08 (95% CI: 0.06-0.10) per 1000 catheter-days ( Figure S2).…”
Section: The Incidence Of Tivap-related Vtementioning
confidence: 99%
“…Additionally, compared with Hickman catheters, we also detect a trend for lower risk of VTE in the TIVAP groups (OR = 0.75, 95% CI: 0.37-1.50), but the result was not significant (P = .413). The results were Preferred venous access site Upper-extremity vein 7,19,20,25,30,31,41,42,59,64,67,69,91 3 .029…”
Section: The Ors Of Tivap-associated Vtementioning
confidence: 99%
See 3 more Smart Citations